(untitled) - Novotna, Jana; Novak Sedlackova, Alena (Doprava a spoje, 2011)
Today the most advanced modern screening technology used for security checks are body scanners. They have started an introduction of extensive discussion about making images which lay bare details of human body. Reservations concerning the impact on health and privacy of passengers who are the subject of detection control. Some detection technologies (body scanners) have the ability to create detailed images of the human body and thus reveal the facts about health (prostheses, joint replacements). These personal data are protected, the legal framework determines strict rules of making and manipulation with these data.